PROSES PENDIDIKAN INSAN KAMIL DI PONDOK SUFI ILMU SYATHTHARIAH PONDOK PESANTREN SUMBER DAYA AT-TAQWA TANJUNGANOM NGANJUK JAWA TIMUR - MUNAWAR RAHMAT (Al Qalam, 2010)
This study tries to explore the education process of the perject man (insan kamil) in the sufi center/ zawiyyah of Ilmu Syaththariah. This study finds several points: firstly, in the Ilmu Syaththariah perspective, Wasithah is the elite respondent (the only reference) in having a religious. He is al-muthohharun (yang disucikan Tuhan) who is given ability to understand the Qur'an. The main fumtion of Wasithah is as the people of invocation (ahladz dzikri), uniting the human essence with the God essence in order that man can absolutety worship the God essence (not His name) when he conducts the religious activities. In praying, man must remember God in order that he is not sentenced to be negligent because one who is negligent to remember God is judged to come into the hell. Secondly, knowing the divine essence through being the people of invocation (ahli zikir) becomes the first step in the process of walking the way of being the perfect man. Then, it is followed by performing spiritual guide's advice wholeheartedly with heart, spirit, and intelledual intuition that always remember the essence of divine mystery. Thirdly, the education process of the perfect man emphasizes the consciousness of the discriples that being the perfect man is due to God's guidance. Therefore, the disciples are resuscitated in order to always hope obtaining His forgiveness, His merry, His help, His virtue, and always hope the Wasithah's grace and blessing. Man also hopes the easiness in performing all spiritual guides' advices until he reaches the spiritual degree (martabat) of the perfed man. Fourthly, the concept of the pe,fect man in the Ilmu Syaththariah perspective can be implemented in the education institutions. Based on the surory, it shows that the students who become the Syaththariah community look more faithful in the observance ef religious obligations than those who do not involve in this the Syaththariah community in the same education institutions.